Base-modified DNA labeled by [Ru(bpy)(3)](2+) and [Os(bpy)(3)](2+) complexes: construction by polymerase incorporation of modified nucleoside triphosphates, electrochemical and luminescent properties, and applications - Vrábel, Milan; Horáková, Petra; Pivonková, Hana; Kalachova, Lubica; Cernocká, Hana; Cahová, Hana; Pohl, Radek; Sebest, Peter; Havran, Ludek; Hocek, Michal; Fojta, Miroslav (Chemistry (Weinheim an der Bergstrasse, Germany), 2009)
Modified 2'-deoxynucleoside triphosphates (dNTPs) bearing [Ru(bpy)(3)](2+) and [Os(bpy)(3)](2+) complexes attached via an acetylene linker to the 5-position of pyrimidines (C and U) or to the 7-position of 7-deazapurines (7-deaza-A and 7-deaza-G) have been prepared in one step by aqueous cross-couplings of halogenated dNTPs with the corresponding terminal acetylenes. Polymerase incorporation by primer extension using Vent (exo-) or Pwo polymerases gave DNA labeled in specific positions with Ru(2+) or Os(2+) complexes. Square-wave voltammetry could be efficiently used to detect these labeled nucleic acids by reversible oxidations of Ru(2+/3+) or Os(2+/3+). The redox potentials of the Ru(2+) complexes (1.1-1.25 V) are very close to that of G oxidation (1.1 V), while the potentials of Os(2+) complexes (0.75 V) are sufficiently different to enable their independent detection. On the other hand, Ru(2+)-labeled DNA can be independently analyzed by luminescence. In combination with previously reported dNTPs bearing ferrocene, aminophenyl, and nitrophenyl tags, the Os-labeled dATP has been successfully used for "multicolor" redox labeling of DNA and for DNA minisequencing.
Keywords: DNA-Directed DNA Polymerase; ruthenium; DNA; reagencia zkříženě vázaná; Staining and Labeling; Color; DNA-dependentní DNA-polymerasy; Luminescence; barvení a značení; Cross-Linking Reagents; Osmium; elektrochemie; barva; osmium; Oligonucleotides; oligonukleotidy; luminiscence; Electrochemistry; Oxidation-Reduction; oxidace-redukce; Ruthenium